Diagnosis and treatment of pediatric arterial stenosis associated with neurofibromatosis type 1 - Haichong Li; Hanwen Zhang; Jun Cao; Dong Guo; Xuejun Zhang; Ziming Yao (BMC Pediatrics)
Abstract Background Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder affecting multiple systems. However, arterial stenosis is a rare manifestation in patients with NF1. Since the symptoms of arterial stenosis caused by NF1 are often atypical and have a high under-diagnosis rate, this can lead to serious complications such as hypertension, ischemic stroke, or even death. The aim of our research is to analyse the clinical characteristics of arterial stenosis in pediatric patients with NF1 and to summarise its diagnosis, treatment and prognosis. Methods We conducted a retrospective review of data from patients with NF1 treated at Beijing Children’s Hospital from 2016 to 2020. Patients diagnosed with arterial stenosis, identified through clinical symptoms, physical examination, arterial ultrasonography, or imaging studies, were included in this study. These patients received symptomatic drug and/or surgical treatments and were followed up regularly. We summarized demographic characteristics, sites of arterial stenosis, clinical manifestations, and treatment outcomes. Result Among the 258 patients with NF1 treated at our hospital, 12 (4.7%) had arterial stenosis, comprising 9 males and 3 females with a median age of 7 years (range: 1–14 years). Renal artery stenosis was diagnosed in 7 patients (58.3%), while internal carotid artery (ICA) stenosis was diagnosed in 5 patients (41.7%). The predominant symptoms of renal artery and ICA stenosis were renal hypertension and convulsions, respectively. Antihypertensive drugs were effective in 5 patients with renal hypertension; 2 patients required balloon dilatation of the renal artery due to inadequate response to medication. Oral antiepileptic treatment was effective in 3 patients with ICA stenosis, and encephaloduroarteriosynangiosis was effective in the remaining 2 cases. The follow-up period ranged from 2 to 6 years, with a median duration of 3 years. No deterioration or mortality was observed during the follow-up period. Conclusions Arterial stenosis was present in approximately 4.7% of patients with NF1, predominantly affecting the renal artery and ICA. Renal hypertension and convulsions were the primary symptoms of renal artery and ICA stenosis, respectively. Early diagnosis and intervention can substantially improve the prognosis of these patients.